Local Adaptation Strategies of a Coastal Community during Cyclone Sidr and their Vulnerability Analysis for Sustainable Disaster Mitigation Planning in Bangladesh (Journal of Bangladesh Institute of Planners, 2012)
Social vulnerability to disasters refers to the inability of a society and it’s people to withstand adverse impacts from multiple stresses to which they are exposed. Using a combination of geographical and social research methods, this paper examines the people’s (re)action and responses during cyclone Sidr 2007 at Baniasanta union of Dacope Upazila in Bangladesh. Finding shows that their adopted strategies to cope with cyclone address their vulnerability and it is necessary to integrate their local wisdom of living with unnatural situation into the future planning and development process of the coastal belt. Accordingly, the plans and development should not only be necessity, but also be accepted by the local community.DOI: http://dx.doi.org/10.3329/jbip.v2i0.9576  Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 158-168